Global strategy for the conservation and use of Musa genetic resources - MusaNet; Laliberte, B. (Bioversity International, 2016)
The Strategy has been updated by Musa genetic resources and breeding experts within the framework of MusaNet, which has the mandate to oversee the implementation and further development of the Strategy.